Developments in Non-Intercalating Bacterial Topoisomerase Inhibitors: Allosteric and ATPase Inhibitors of DNA Gyrase and Topoisomerase IV - Scott Grossman; Colin W. G. Fishwick; Martin J. McPhillie (MDPI AG, 2023)
Increases in antibiotic usage and antimicrobial resistance occurrence have caused a dramatic reduction in the effectiveness of many frontline antimicrobial treatments. Topoisomerase inhibitors including fluoroquinolones are broad-spectrum antibiotics used to treat a range of infections, which stabilise a topoisomerase-DNA cleavage complex via intercalation of the bound DNA. However, these are subject to bacterial resistance, predominantly in the form of single-nucleotide polymorphisms in the active site. Significant research has been undertaken searching for novel bioactive molecules capable of inhibiting bacterial topoisomerases at sites distal to the fluoroquinolone binding site. Notably, researchers have undertaken searches for anti-infective agents that can inhibit topoisomerases through alternate mechanisms. This review summarises work looking at the inhibition of topoisomerases predominantly through non-intercalating agents, including those acting at a novel allosteric site, ATPase domain inhibitors, and those offering unique binding modes and mechanisms of action.